Naringin is a promising natural compound for therapy of iron-overload disorders - Mehrdad Jahanshahi; Masoumeh Khalili; Asra Margdari; Mahdi Aalikhani (Universidade de São Paulo, 2022)
Abstract Naringin has been shown to exhibit satisfying iron chelation capacity. Considering the side effects of routinely-used iron chelator (desferrioxamine, DFO), we decided to evaluate the iron chelation potency of naringin to discover whether or not it can be a promising natural substitute for treatment of excessive iron-related diseases. 35 mice were classified into five groups of 7 and subjected to iron dextran administration to induce the iron-overload condition. Iron-overloaded mice were then treated with normal saline (as control), naringin or DFO Morphology changes, and iron deposition in liver tissues were studied using H&E and Perl's staining. The results revealed that naringin is more potent than DFO in removing excessive iron ions deposited in liver tissues, indicating that naringin is a promising natural compound for therapy of iron overload disorders.